AN ANALYSIS OF COMPREHENSIBILITY OF READING TEXT IN TEXTBOOK “BAHASA INGGRIS FOR GRADE XII SMA/MA” (A STUDY CONDUCTED AT SMA N 1 MOTOLING TIMUR) - Kontu, Sitti S.; Oroh, Elizabeth Z.; Tuna, Jim R. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study aimed to describe the comprehensibility of reading texts in textbook “Bahasa Inggris for Grade XII SMA/MA”. This research design using quantitative method that involved 25 participants of 12TH grade students SMA N 1 Motoling Timur in academic year 2021/2022. The author used cloze test consisted of 8 texts to measure the comprehensibility of reading texts in textbook. Where the “exact words/ real words from texts were missing” used as evaluation method, than the score calculated by using percentage formula, after collect all score from students answers to got the comprehensibility of reading texts in textbook and the result come out under 50% that’s mean the text was not comprehensible.